1913 N.H. Laws 639 - (:unkn) unknown (My University, 1913)
An Act to Regulate the Transportation of Dynamite, Gunpowder and Explosives, ch. 128, § 1: It shall be unlawful to transport, carry, or convey from one place in this state to another place in this state, any dynamite, gunpowder, or other explosive on any vessel or vehicle of any description operated by a common carrier, which vessel or vehicle is carrying passengers for hire
Keywords: GUNPOWDER - TRANSPORTATION